Emerging Technologies to Control Oocyte Apoptosis Are Finally Treading on Fertile Ground - Jonathan L. Tilly (The Scientific World Journal)
As the medical community strives to improve on the efficacy of anticancer treatments, a critical issue not to be overlooked since the overall quantity of life has been substantially increased in many cancer survivors is the quality of that life post-therapy. Indeed, one of the most worrisome side effects of conventional cancer treatments is damage to the gonads. This problem is compounded in females since the ovaries, unlike the testes, are incapable of germ cell renewal in postnatal life. As a consequence, the inappropriate destruction of female germ cells (oocytes) following exposure to chemotherapeutic drugs and radiation is irreparable, often leading to premature menopause and infertility [1]. Considering recent estimates that 1 in 52 human females between birth and age 39 (i.e., the pre-reproductive and reproductive years) will be diagnosed with, and presumably treated for, cancer [2], new strategies to minimize or prevent gonadal damage during such treatments would have a profound positive impact on millions of lives.